2021
DOI: 10.1080/02656736.2021.1954245
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of MR-HIFU and US-HIFU in treating uterine fibroids with the volume <300 cm3: a meta-analysis

Abstract: Background: High-intensity focused ultrasound (HIFU) is a promising and non-invasive therapy for symptomatic uterine fibroids. Currently, the main image-guided methods for HIFU include magnetic resonance-guided (MR-HIFU) and ultrasound-guided (US-HIFU). However, there are few comparative studies on the therapeutic efficacy and safety of MR-HIFU and US-HIFU in treating symptomatic uterine fibroids with a volume <300 cm 3 . Objective: We performed this meta-analysis to evaluate the efficacy and safety of MR-HIFU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…Several studies showed lower frequency of major complications and treatable minor complications, in which skin redness, abdominal pain or discomfort and sciatic nerve paresthesia or simply leg pain are the most common. SAE occur in less than 0.5% of cases including second degree skin burn, lesions to bowel, ureter and bladder [29]. These complications occur when organs are in acoustic pathway or when the thermal effect induces inflammatory response and edema [21].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies showed lower frequency of major complications and treatable minor complications, in which skin redness, abdominal pain or discomfort and sciatic nerve paresthesia or simply leg pain are the most common. SAE occur in less than 0.5% of cases including second degree skin burn, lesions to bowel, ureter and bladder [29]. These complications occur when organs are in acoustic pathway or when the thermal effect induces inflammatory response and edema [21].…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes of HIFU depend on different matters. According to myoma localization, it is observed that intramural fibroids [11] with volume under 300 cm 3 [29] show higher volume reduction results due to less deep tissue and scared blood supply, as compared to transmural and submucosal uterine fibroids. Regarding signal intensity of fibroids, two retrospective studies reported contradictory results about fibroid shrinkage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations